A sensor based on high-sensitivity multi-pass resonant photoacoustic spectroscopy for detection of hydrogen sulfide. (April 2023) - Zhang, Mingke; Gao, Guangzhen; Jiang, Yuhao; Wang, Xuan; Long, Fangyu; Cai, Tingdong
Highlights: A high-sensitive multi-pass photoacoustic spectroscopy sensor is developed for hydrogen sulfide. With the enhancement of effective laser power in the multi-pass PA cell, the 2 f -signal of the target H2 S line has a ∼ 8 times improvement. The minimum detection concentration of the system can reach 0.13 ppm with a 1-minute averaging time. Abstract: A high-sensitive tunable diode laser sensor based on photoacoustic spectroscopy and multi-pass absorption spectroscopy is developed for hydrogen sulfide (H2 S) detection using a target absorption line at 6287.005 cm −1 . Two spherical concave mirrors are utilized as the reflectors to make the laser beam pass through the photoacoustic cell for 24 times. The wavelength modulation spectroscopy technique with second harmonic detection (WMS- 2f ) method is employed to reduce external interference and increase the detection sensitivity. With the enhancement of the effective laser power in the multi-pass PA cell, the photoacoustic 2f signal of the target H2 S absorption line has a ∼ 8 times improvement compared to the sensor system without multi-pass cell. Based on the results of Allan variance analysis, the minimum detection concentration of the system could reach 0.68 ppm with a 10-s average time and it can be further lowered down to ∼ 0.1 ppm when a 1-minute averaging time is used. The linear responsivity of the multi-pass PA spectroscopy sensor is estimated to be ∼ 0.00112 mV/ppm by linear fitting for a continuous flow gas measurement results. The excellent performance validates the potential of the sensor for field application.